Construction of an EPO (Human-Erythropoietin) Synthetic Gene Through a Recurvise-PCR Method - Fuad, Asrul Muhamad; Gusdinar, Tutus; Retnoningrum, Debbie Sofie; Natalia, Dessy (ANNALES BOGORIENSES, 2008)
Human  erythropoietin (hEPO)  is an  important glycoprotein  in human  that is coded by a single gene named EPO  (eryhtopoietin). EPO  is  a  glycoprotein  hormone  that  promotes  erythropoiesis,  which  is  the  formation process of mature  red  blood  cell  (erythrocytes)  in  human  bodies.  It  is  widely used  for  treatment  of anemia  in patient  With  chronic  renal failure.  Therefore  EPO has  been classified  as hematopoietic cytokine. Recombinant hEPO  (rhEPO)  has  been  commercially  available,  such  a  Epogen.  It  is  produced  in  mammalian  cell, such  as CHO  (Chine  e hamster ovary) cells  for  the  reason of  its complex structure as a glyco-protein. In  an effort  to  use and optimize heterolgous EPO gene expression  in  an  alternative eukaryotic  host  cells  such  as  yeast, an  EPOsynthetic  gene  (EPOsyn)  was  constructed.  The  synthetic  gene  had  been designed to contain  optimaI Pichiapastoris codon usage . It had  been constructed by a  recursive-PCR method  in  two-step PCR reactions. The gene was assembled  from  8 single strands synthetic  oligonuclotides having an average  length of 90 nt with 20  to 30 overlap  region  between  two  adjacent  oligos. The  synthetic  gene  has  less  GC  content  (4-.3 1%)  compared  its native (human) gene (59.08%). The synthetic gene has  been cloned  in  pCR2.1  cloning plasmid and sequenced. From  8  independent clones,  it was revealed  that  the error  rate  was  1.59%,  in which  1.42% was due  to deletions and 0.17% due  to substitutions. Design of  the gene sequences, construction method and DNA sequence analysis of  the gene will  be discussed  in  this  paper.   Keywords: Human erythropoietin (hEPO), erythropoiesis  EPOsynthetic  gene, recursive-PCR, Pichiapastoris, hematopoietic cytokine.